2015
DOI: 10.1097/cad.0000000000000235
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effect and mechanism inducing cell death of α-mangostin liposomes in various human carcinoma and normal cells

Abstract: The aims of this study were to develop α-mangostin liposomes as well as to evaluate their physicochemical properties and cytotoxic activity. α-Mangostin liposomes were prepared using the reverse-phase evaporation method with lipid composition of phosphatidylcholine to cholesterol at 7 : 3 molar ratios; their physicochemical properties and antiproliferative activity were assessed using an MTT assay in four human carcinoma cells [that is, human lung epithelial carcinoma (Calu-3), human colon carcinoma (HT-29), h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…In our work, we have demonstrated that [3] and [4] are two new compounds that showed the highest TS and potencyselectivity expression values among the compounds tested, and they exhibited much less keratinocyte toxicity compared to doxorubicin and 5-FU (Figure 4). Chemical modification of these lead compounds by introduction of appropriate functional groups is a crucial step towards manufacturing new types of anticancer drugs with reduced keratinocyte toxicity.…”
Section: Future Directionsmentioning
confidence: 78%
See 3 more Smart Citations
“…In our work, we have demonstrated that [3] and [4] are two new compounds that showed the highest TS and potencyselectivity expression values among the compounds tested, and they exhibited much less keratinocyte toxicity compared to doxorubicin and 5-FU (Figure 4). Chemical modification of these lead compounds by introduction of appropriate functional groups is a crucial step towards manufacturing new types of anticancer drugs with reduced keratinocyte toxicity.…”
Section: Future Directionsmentioning
confidence: 78%
“…Compound [3] induced apoptotic cell death in a human OSCC cell line, possibly by down-regulating the glycerophospholipid pathway. Quantitative structure−activity relationship analysis demonstrated that the tumor specificities of [3] and [4] Previous studies have focused on the mechanism of apoptosis induction by anticancer drugs rather than the demonstration of their tumor specificity.…”
Section: Abstract Most Current Anticancer Drugs Have Shown Excellentmentioning
confidence: 99%
See 2 more Smart Citations
“…α-Mangostin has been extracted from the rind of mangosteen fruit using 1,2-propanediol-betaine, [2] ethyl acetate, [3] and supercritical CO 2 [4] as a green solvent, and from the pericarp with water, [5] and water at 65 C [6] and purification through solid phase extraction. [7] α-Mangostin has been reported to have anti-acne activity, [8] inhibit mutant IDH1, [9] prevent and treat hepatocellular carcinoma, [10] and exhibit antiinflammatory, [11][12][13][14] antibacterial, [15,16] antitumor, [17,18] and antimetastatic properties in many cancer cell types. [19] The biological activities and pharmacological properties of α-mangostin as an antineoplastic agent, antioxidant, antiproliferation agent for the induction of apoptosis, [20] and as a lysine-specific demethylase 1 (LSD1) inhibitor against tumor metastasis [21] have been reviewed.…”
Section: Introductionmentioning
confidence: 99%